Studi Gambaran Pengetahuan Guru PAUD tentang Gizi Anak dalam Pendidikan Anak Usia Dini di PAUD Kecamatan Remboken - Eduard Jeconya Lengkong (Jurnal Ilmiah Wahana Pendidikan, 2022)
Nutrition is an important element in the process of growth and development of children. Teachers' knowledge about nutrition is one of the tasks to fulfill their competence as a teacher. The purpose of this study was to describe teachers' knowledge of child nutrition in early childhood education. The research method used is descriptive research with a quantitative approach. The results of this study show that the average percentage of teacher knowledge about child nutrition in early childhood education is 50%, meaning that teachers must continue to increase their knowledge of child nutrition in early childhood education. Both knowledge about children's nutritional needs, nutrition in early childhood education, and nutrition in the implementation of learning must continue to be improved even though teachers' knowledge of nutrition in early childhood education has reached 100%.